2004
DOI: 10.1111/j.0022-0477.2004.00883.x
|View full text |Cite
|
Sign up to set email alerts
|

Ground cover recovery patterns and life‐history traits: implications for restoration obstacles and opportunities in a species‐rich savanna

Abstract: Summary 1We identified species with low re-colonization potential, which could be used as indicators of recovery of species-rich pine savannas, by comparing the ground-cover flora of a 64-year-old slash pine plantation (recovery site) with that of a nearby natural longleaf pine savanna (reference site). We also determined life-history traits that were useful predictors of recolonization potential. 2 The high floristic overlap in species between reference and recovery sites and similar species richness at scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
121
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(130 citation statements)
references
References 46 publications
6
121
0
3
Order By: Relevance
“…Despite our conclusions about the value of a more synthetic trait for comparative studies, we recognize that site-specific studies focused on understanding the relationship of specific mechanistic traits to disturbance have often helped pinpoint specific mechanisms of change (Dzwonko and Loster, 1992;Matlack, 1994;Graae and Sunde, 2000;Kirkman et al, 2004;Mayfield et al, 2006). In contrast, habitat traits may not necessarily reveal such mechanisms, but only patterns of change.…”
Section: Discussionmentioning
confidence: 91%
“…Despite our conclusions about the value of a more synthetic trait for comparative studies, we recognize that site-specific studies focused on understanding the relationship of specific mechanistic traits to disturbance have often helped pinpoint specific mechanisms of change (Dzwonko and Loster, 1992;Matlack, 1994;Graae and Sunde, 2000;Kirkman et al, 2004;Mayfield et al, 2006). In contrast, habitat traits may not necessarily reveal such mechanisms, but only patterns of change.…”
Section: Discussionmentioning
confidence: 91%
“…Conservation of ground floras with suites of species which are largely absent from anthropogenically disturbed or younger forests is an increasing concern for biodiversity and natural heritage conservation (Gilliam and Roberts, 2003;Whigham, 2004;Flinn and Vellend, 2005;Gilliam, 2007). Even within old-growth or older forests, frequently the ground-flora composition has been altered by anthropogenic legacies of grazing or soil disturbance and sensitive or dispersallimited species may be absent (Kirkman et al, 2004;Harrelson and Matlack, 2006). In Ohio, Hutchinson et al (2005b) found that five years of prescribed fire treatments in a previously fire-suppressed forest resulted in moderate increases in small-scale ground-flora species richness, particularly contributed by increases in grasses, summer forbs, and seed-banking species.…”
Section: Discussionmentioning
confidence: 99%
“…A song of the good green grass A song no more of the city streets Walt Whitman (1882) Leaves of Grass Sea-level rise: Donoghue 2011 Restoration, intervention, and adaptive management: Mooney 1988, Pauly 1995, Kirkman et al 2004, Jackson and Hobbs 2009, Howes et al 2010, Hobbs et al 2011, Lynas 2011, Marris 2011 http://naturalhistorynetwork.org/ The (new) Nature Conservancy: Fairbank, Maslin, Maullin, Metz & Associates 2010, Dunkel 2011, Kareiva 2011Values and ethics: Leopold 1949, Wilson 1984, Crompton 2011, Patten and Smith-Patten 2011 REED NOSS is professor of biology at the University of Central Florida and president of the Florida Institute for Conservation Science. He has served as editor-in-chief of Conservation Biology and president of the Society for Conservation Biology.…”
Section: The Future?mentioning
confidence: 99%